Psychological and Social Determinants related to the Development of Mental Disorders in Puerperium: A integrative review (Research, Society and Development, 2021)
Understand the scientific evidence about psychological and social determinants related to the emergence of mental disorders in the puerperium. The present study was developed through an integrative review of an exploratory caracter, the databases used in this research are indexed: LILACS (Latin American and Caribbean Literature in Health Sciences) and MEDLINE (Medical Literature Analyses and Retrieval System Online). During the research it was evidence that psychological changes and social factors in the lives of women can trigger psychosocial problems causing serious mental disorders. Affective and professional monitoring must be necessary from the beginning of gestational life, to the postpartum and puerperium period, in order to prevent damage to the woman's physical and mental health. Therefore, it is important to know all the social and psychological factors of these women in order to carry out planning, support and assistance.